9x-4(x-3)=x+120

Simple and best practice solution for 9x-4(x-3)=x+120 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x-4(x-3)=x+120 equation:


Simplifying
9x + -4(x + -3) = x + 120

Reorder the terms:
9x + -4(-3 + x) = x + 120
9x + (-3 * -4 + x * -4) = x + 120
9x + (12 + -4x) = x + 120

Reorder the terms:
12 + 9x + -4x = x + 120

Combine like terms: 9x + -4x = 5x
12 + 5x = x + 120

Reorder the terms:
12 + 5x = 120 + x

Solving
12 + 5x = 120 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
12 + 5x + -1x = 120 + x + -1x

Combine like terms: 5x + -1x = 4x
12 + 4x = 120 + x + -1x

Combine like terms: x + -1x = 0
12 + 4x = 120 + 0
12 + 4x = 120

Add '-12' to each side of the equation.
12 + -12 + 4x = 120 + -12

Combine like terms: 12 + -12 = 0
0 + 4x = 120 + -12
4x = 120 + -12

Combine like terms: 120 + -12 = 108
4x = 108

Divide each side by '4'.
x = 27

Simplifying
x = 27

See similar equations:

| 23x+47=12 | | 36=6y+9x | | -18x-42=8x-16+16 | | 3t+31=-56 | | 6x+62=2x+30 | | 7n^2+19n=6 | | 3b+4/3=b-4/2 | | -5(x+3)-16=12+2 | | -.5=.5-1 | | 4x^2-19x+39=5x+4 | | b-1+b-1+b+3+2b=31 | | 17n^2+19n=6 | | 4n+5=n+35 | | 10y-6=-8-y | | 0.5m+1=21 | | -2[-2(y+1)-3(y-2)]=8 | | 0.1(x+20)-5=0.25(2x+8) | | -26.25-15.5x=-15.5x+11.78 | | 6y-4=-8+10y | | 3x-5-5x=-13 | | N+4+9= | | X+28=x+x+2 | | c*5=30 | | -26.25-15.5x=-15.5+11.78 | | 6x^2+7-49=0 | | -8d+96=3d-3 | | 36=9x+6y | | 3/7=c+4/35 | | r^4+2r^3+10r^2+18r^1+9=0 | | 5k-4(k+4)=2 | | 0.625y+8=5+0.5y | | b+4/=7/4 |

Equations solver categories